El matrimonio de adolescente y su afectación a los derechos constitucionales - Ruiz Mena, Pedro Fabian (2014)
This thesis has the overall aim to analyze the fundamental guarantee of the right to integral development, understood as a process of growth, maturation and deployment of personality, we would question truncated in adolescents who have not attained fifteen years of age and contract marriage , also resulting in this despicable act Teens reason that at this age, and as is evident in Ecuador do not really have the proper physical and psychological maturity to start socially responsible life necessarily implies marriage, why which includes a study of comparative law with laws of other countries in Latin America. There is also analysis of different writers who deal with the subject in question, gathering information from very ancient times where precisely indicate the ways of forming families in those days and what were its causes , so it has been possible to conclude , that sexual integrity is a very important aspect in humans and is a right recognized fully by the universal declaration of human rights, Finally it is recommended that an amendment to the civil code, which prohibits holding marriage to not meet at least fifteen years of age and in this way protect their right to full development recognized by the constitution, and thus ensure that young people reach full maturity and can make their own decisions responsibly towards marriage our society organization and consequently achieve the balance we crave according to our age. This legal research is organized into six chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter the methodology used in the research in question is described, the methods used, types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained by interviewing authorities located Quevedo, plus surveys of lawyers in free practice. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter discusses the proposal, objectives, description of the ' proposal, beneficiaries and social impact, etc.